Controllability of Hilfer Fractional Differential Systems with Non-Dense Domain. (3rd October 2019) - Singh, Vikram
Abstract: In this paper, some exact controllability results are investigated for an integral solution of a non-densely defined abstract fractional differential system involving Hilfer fractional derivative. We tend to implement semigroup theory, fractional calculus, and measure of noncompactness to obtain the main results by fixed point technique. Finally, an application is given to illustrate the obtained results.